Implementasi Undang-Undang Keterbukaan Informasi Publik terhadap Transparansi Pejabat Publik di Indonesia - Sukendi; Harmonis (PT. Hasba Edukasi Mandiri, 2026)
Public information disclosure is a crucial component of realizing transparent, accountable, and democratic governance. This study aims to analyze the implementation of Law Number 14 of 2008 concerning Public Information Disclosure on the transparency of public officials in Indonesia and to identify obstacles to its implementation. The research method used is normative juridical with a legislative approach, a conceptual approach, and a case study approach. The research data were obtained through a literature review sourced from laws and regulations, books, scientific journals, and official data from the Central Information Commission of the Republic of Indonesia. Research shows that the implementation of the Public Information Disclosure Law has encouraged increased public information disclosure in Indonesia. The Central Information Commission of the Republic of Indonesia, through the launch of the 2025 Public Information Disclosure Index (IKIP), emphasized that information disclosure is a strategic instrument in supporting good and accountable governance. However, the results of the 2025 Public Information Disclosure Monitoring and Evaluation (Monev) indicate that transparency implementation is still not optimal because of the 387 public bodies monitored, 121 public bodies are categorized as